Pengaruh Makroekonomi terhadap Yield Spread Obliglasi Indonesia Berdenominasi Rupiah - , Anup Kumar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia bond market is developing rapidly but not much is understood in the terms of macroeconomic factors that could influence the yield spread of the Indonesian Rupiah denominated bond. Based on a multifactor model, this paper examines the impact of six macroeconomics factor namely: interest rate (INT), inflation rate (INF), exchange rate (KURS), country rating (PHN), bond index (IB) and Indeks Harga Saham Gabungan (IHSG) on bond yield spread of the Indonesia Government Securities (IGS) and Corporate Bonds for a periode between December 2009 to June 2012. The findings support the expected hypotheses that INF are the major drivers that influence the changes in yield spreads. However INT, KURS, PHN and IB have weak and no influence on yield spreads respectively. Whilst IHSG has significant influence only on the yield spread with longer term maturing bond.